Islamic Religious Leaders’ Participation in Educational Management in Thailand - บุญนรากร สกุณา; ภัสสรศิริ นิตยา; พ่วงสมจิตร์ ชูชาติ; เจนอักษร นภดล (Al-HIKMAH Journal, 2018)
National Education Act B.E.2542 (1999) and Amendments (Second National Education Act B.E. 2545 (2002) stipulated that education provision shall be based on the principle which all segments of society participating in provision of education and partnerships with religious institutions. The purposes of this documentary research were to study and analyze the states of Islamic religious leaders’ participation in educational management in Thailand from 1946 to 2011. The research data were obtained from primary and secondary documentary sources. There were 25 documents comprising 10 primary documents and 15 secondary documents available at libraries and work agencies and on electronic databases. The research instruments comprised a document quality evaluation form and a data recording form. The methods of data collection involved: searching published, unpublished, paper and electronically stored documents; document selection; and document evaluation. The data were analyzed by using content analysis. The research findings concluded that Islamic religious leaders participated in all 3 education systems and 4 aspects of educational management in Thailand namely: 1) schools establishment by establishing schools, training centers for preschool, training centers for ethics in mosque, Islamic education centers and community education centers; 2) educational administration by being school owner, allow using the musjid’s building to be a place of learning 3) teaching and learning support by the propagation of Muslims, training prenuptial, and counseling about religion and lifestyle of the Muslims, and 4) resources and investment in education by donated land to build a school building.